Budaya Organisasi, Iklim Komunikasi Organisasi Dan Kinerja Karyawan Di PT. Mitra Sejati Rezeki - Mega Sihombing; Setiamenda Ginting; Evi Enitari Napitupulu; Cadra Halawa; Viktoria Zai (Universitas Sari Mutiara Indonesia, 2022)
This research aims to determine and explain the significant influence of organizational culture and organizational communication climate simultaneously and partially on employee performance at PT. A True Partner of Fortune. This type of research uses explanatory research methods, namely research that explains the relationship between variables and tests hypotheses that have been previously formulated. The population in this study were all employees of PT. A True Partner of Fortune. The sample in this study was 86 respondents. Proportionate stratified random sampling technique was used to take the sample. The analysis model used in this research is Multiple Linear Regression with the help of the SPSS version 16.0 for Windows program. The partial research results showed that organizational culture variables had a significant effect on employee performance by 16.6% and organizational communication climate had a significant effect on employee performance by 68.4%. Simultaneously, the organizational culture variable and organizational communication climate variable have a significant effect on employee performance by 51.3%.